2021
DOI: 10.1021/acsmacrolett.1c00220
|View full text |Cite
|
Sign up to set email alerts
|

1D-Confinement Inhibits the Anomaly in Secondary Relaxation of a Fluorinated Polymer

Abstract: We present an experimental study of the dynamics of a well-pronounced secondary relaxation observed in bulk and ultrathin films of the fluorinated copolymer poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP). In proximity to the glass transition, an anomalous phenomenon is observed: the β-relaxation slows down upon heating. Measurements as a function of the film thickness show that this exceptional behavior gradually vanishes upon confinement at the nanoscale level. Regardless of sample size, the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Comparing with previous literature reports, and taking into consideration the intensity and position of the peaks, we were able to assign the low-temperature process to the local β-relaxation of PVDF related to local motions of polar groups in the polymer [73][74][75][76]. As the temperature was further increased (T > −60 • C), the relaxation peaks suffered important changes.…”
Section: Dielectric Spectroscopy Studies In Pvdf and Its Copolymerssupporting
confidence: 67%
See 1 more Smart Citation
“…Comparing with previous literature reports, and taking into consideration the intensity and position of the peaks, we were able to assign the low-temperature process to the local β-relaxation of PVDF related to local motions of polar groups in the polymer [73][74][75][76]. As the temperature was further increased (T > −60 • C), the relaxation peaks suffered important changes.…”
Section: Dielectric Spectroscopy Studies In Pvdf and Its Copolymerssupporting
confidence: 67%
“…Just at the transition temperatures (~47-57 • C), a small kink can be detected in the relaxation plot. Finally, very recently, Napolitano and collaborators observed an anomalous behavior in the local relaxation of PVDF copolymers with hexafluoropropylene (HFP) [76]. In their work, the dielectric relaxation experiments showed that, in the vicinity of T g , the PVDF-HFP copolymers displayed a so-called "anomalous minimum" in the local relaxation.…”
Section: Dielectric Spectroscopy Studies In Pvdf and Its Copolymersmentioning
confidence: 98%
“…Recently, the same group revealed that the exceptional secondary relaxation of poly­(vinylidene fluoride-hexafluoropropylene) (P­(VDF-HFP)) behavior gradually vanished upon confinement at the nanoscale level. This was explained by the presence of adsorbing walls inducing an increase in T g , which counterbalanced the asymmetry in the double-well potential responsible for the molecular motion . The effect of roughness of substrate on the relaxation of P4ClS and P2VP was studied, as shown in Figure p,q.…”
Section: Interface Study By Model-based Measurementmentioning
confidence: 99%
“…This was explained by the presence of adsorbing walls inducing an increase in T g , which counterbalanced the asymmetry in the double-well potential responsible for the molecular motion. 268 The effect of roughness of substrate on the relaxation of P4ClS and P2VP was studied, 269 as shown in Figure 16p,q. The increase of roughness led to the fast relaxation of P4ClS and the asymmetric broadening of relaxation peaks toward high frequency but had little effect on the P2VP.…”
Section: Structure Orientation Of Functional Groups and Molecular Chainsmentioning
confidence: 99%